The rough patch - Lies, Brian (Greenwillow Books, an imprint of HarperCollinsPublishers, 2018)
Farmer Evan and his dog do everything together and, especially, in the garden but when his dog passes away Evan lets his garden fill with weeds until a pumpkin vine brings new hope.
Keywords: Loss (Psychology) -- Fiction; Gardens -- Fiction; Dogs -- Fiction; Farm life -- Fiction